Myth of Criminality - Kilmkaitė-Petraitienė, Lina (Sociologija. Mintis ir veiksmas, 2015)
The aim of the article is to analyze the notion of myth of criminality, a view on the conditions of justice built around stereotypes that are formed in the interaction between the members of society, mass media and the institutions of power. The author attempts to develop the analysis on a few levels giving special attention to issue of death penalty in Lithuanian society: the relation between social understanding of the conditions of justice and the reality of justice; the role of the mass media and institutions of power in constructing knowledge of the crime situation; the way that the myths depict the situation; the main features of myth of criminality; the functions of myth of criminality in social life. The author argues that the task of conceptualizing the process of the formation of myths of criminality cannot be separated from the critique of those myths. Yet, the risk of recreating the myths in other forms requires to understand the development of the critique as a reflexive task.